PENINGKATAN KOMPETENSI GURU SDN TUNJUNGSEKAR 5 KOTA MALANG DALAM PENYUSUNAN RPP BERBASIS TEMATIK TERPADU MELALUI MODEL DOUBLE EXPERT GROUP JIGSAW - Agus Sriwulan (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2017)
This research aims to enhance the teachers’ competency on Tunjungsekar 5 Elementary School Malang in arranging integrated thematic based lesson plan with Double Expert Groups Jigsaw model. This is a School Action Research consisting 2 cycles. Each of the cycle consists of four stages, planning, implementing, observing, and reflection.The subjects of this research 12 teachers, 9 female teachers and the rest are male teachers, of Tunjungsekar 5 Elementary School Malang year 2016/2017. The data regarding Tunjungsekar 5 Elementary School Malang teachers’ competence in arranging integrated thematic based lesson plan and the implementation of Double Expert Groups Jigsaw model are submitted in observation sheet and questionnaire. The collected data then analyzed with descriptive qualitative analysis technique.The research result of the implementation of Double Expert Groups Jigsaw model shows a significant increase, 52% on the cycle I into 90% on the cycle II. The significant increase also occurred in the Tunjungsekar 5 Elementary School teachers’ competence in arranging integrated thematic based lesson plan from 63% on the cycle I and 82% on the cycle II. Based on the result above, it can be concluded that Tunjungsekar 5 Elementary School Malang teachers’ competence in arranging integrated thematic based lesson plan increases with the help of the effectiveness of Doble Expert Groups jigsaw model implemented by the teachers. Keywords: Double Expert Groups Jigsaw cooperative model, Teachers’ Competence, Integrated Thematic based Lesson Plan